Visitors’ perception image of the Douro demarcated region through social networks - Esteves, Elsa Tavares (2022)
The image of a tourist destination is a strong antecedent of the behavioral intention of tourists, such as the intention to visit/revisit the destination or to recommend others to visit. Therefore, different tourist organizations try to create a robust image for their destinations that helps them to differentiate themselves from others to become competitive. The Douro Wine Region, World Heritage Site since 2001, presents itself as a tourist destination par excellence, for its various attractions. Thus, this exploratory study aims to analyze the presence in social networks of the destination Douro Vinhateiro and identify the dimensions of the destination image. To this end, a work was developed according to the mixed research model; two methodological approaches were adopted - qualitative and quantitative. As a data collection method, in a first phase, the documental analysis was chosen, followed by a qualitative analysis of websites and social networks related to the Alto Douro Wine Region and, in a second phase, a questionnaire was applied to tourists who visited this region. The results showed that the image of the region under study is formed by three main dimensions: the Douro River, the Vineyards, and the City of Porto. Tourists also point to these three dimensions as the main factors associated with this region.